Memoirs of Huseyn Shaheed Suhrawardy with a brief account of his life and work - Talukdar, Mohammad H. R. (Mohammad Habibur Rahman) (University Press, 1987)
Memoirs of a former chief minister of Bengal and prime minister of Pakistan, chiefly on politics in Pakistan; includes his biography by the editor.